2022
DOI: 10.5534/wjmh.200195
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Paternal Age and Sperm DNA Fragmentation: A Systematic Review

Abstract: Purpose Male ageing is often associated with defective sperm DNA remodeling mechanisms that result in poorly packaged chromatin and a decreased ability to repair DNA strand breaks. However, the impact of advanced paternal age on DNA fragmentation remains inconclusive. The aim of the present systematic review was to investigate the impact of advancing paternal age (APA) on DNA fragmentation. Materials and Methods We conducted a thorough search of listed publications in S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 42 publications
3
17
0
Order By: Relevance
“…In the current study, the analysis of 1638 IVF/ICSI cycles showed that the sperm DFI was significantly positively correlated with male age, indicating that the degree of sperm DNA fragmentation increased with age ( Supplementary Table 1 ). This is consistent with the findings of Bellver ( 15 ), Ghanbarzadeh ( 16 ), Zhang ( 17 ), Gonzalez ( 18 ), Lu ( 19 ) and Belloc ( 20 ). The sperm DFI was significantly and positively correlated with abstinence days, semen volume, immotile sperm percentage, sperm high-staining HDS percentage and other parameters, suggesting that the increase in abstinence days may increase semen volume, but the immotile sperm percentage and sperm high-staining HDS percentage may increase at the same time.…”
Section: Discussionsupporting
confidence: 92%
“…In the current study, the analysis of 1638 IVF/ICSI cycles showed that the sperm DFI was significantly positively correlated with male age, indicating that the degree of sperm DNA fragmentation increased with age ( Supplementary Table 1 ). This is consistent with the findings of Bellver ( 15 ), Ghanbarzadeh ( 16 ), Zhang ( 17 ), Gonzalez ( 18 ), Lu ( 19 ) and Belloc ( 20 ). The sperm DFI was significantly and positively correlated with abstinence days, semen volume, immotile sperm percentage, sperm high-staining HDS percentage and other parameters, suggesting that the increase in abstinence days may increase semen volume, but the immotile sperm percentage and sperm high-staining HDS percentage may increase at the same time.…”
Section: Discussionsupporting
confidence: 92%
“…This is the first study to classify the patients according to paternal age and the SDF rate and to correlate with the clinical and laboratory outcomes in the ICSI cycles of donor oocytes. In most of the studies, paternal age correlation was limited to semen parameters like volume, count, motility, morphology, and SDF rates (14,17,30). Female factors like age, ovarian reserve, and oocyte quality play a major role in determining the clinical and laboratory outcomes (10,28,31).…”
Section: Discussionmentioning
confidence: 99%
“…The negative influence of SDF on the laboratory outcomes and clinical outcomes in in-vitro fertilization (IVF) cycles and/or intracytoplasmic sperm injection (ICSI) was reported by various studies and meta-analyses (7)(8)(9)(10)(11)(12)(13). Paternal age has been linked to SDF in various studies; an increase in paternal age has a positive correlation with SDF (14,15). Few studies have reported paternal age of 40 years and above has increased the risk for SDF (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…One proposed mechanism of the adverse reproductive outcomes in natural and assisted reproduction is impaired sperm chromatin integrity and increased DNA fragmentation rates ( 52 ). In a recent systematic review, 17 out of 19 studies demonstrated an association of advanced paternal age with significant increase in DNA fragmentation ( 53 ), mostly measured by Sperm Chromatin Structure Assay ® and sperm chromatin dispersion test. The two studies that did not find the effect of advanced paternal age on sperm DNA fragmentation utilized terminal deoxynucleotidyl transferase-mediated deoxyuridine triphosphate nick end labelling (TUNEL) assay.…”
Section: Impact Of Advanced Paternal Age In Men and On Their Progenymentioning
confidence: 99%